2020
DOI: 10.1177/0269094220968048
|View full text |Cite
|
Sign up to set email alerts
|

Capital ownership, innovation and regional development policy in the economic periphery: An energy industry case

Abstract: This paper examines how far patterns of external ownership affect benefits from industry geographical proximity. The case explores investments in energy and electricity supply in Wales. Geographically related benefits are examined through a Smart Specialisation lens, in the areas of innovation; firm-to-firm interaction; the labour market and public sector intervention. We find evidence that the ownership model or ‘home location’ of key firms is an important factor driving local economic benefits, and explore r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Global systems have long advantaged 'core' regionscountries, regions, cities -and those living in them by directing material, energy and value flows from poorer places (Jones, 2015;Hickel et al 2022), but these resources and the capitals that generate them are degrading in the face of climate change and the over-exploitation of nature. Novel tensions and areas of conflict are emerging, not just with respect to who 'owns' and benefits from increasingly scarce resources, but also in terms of who national and supra-national regulation, and environmentally-oriented trading schemes, will advantageand who can prepare best to take advantage (Jones & Munday, 2020;McAfee, 2022). These tensions are becoming clear in resource rich and (relatedly) relatively poor regions in South and Northand with transnational actors increasingly visible in processes that shape places to capture new and diminishing value, and insure against regulatory and industrial change (Hein et al, 2019;Bueno et a, 2018;Beauchamp & Jenkins, 2020;Feldman et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Global systems have long advantaged 'core' regionscountries, regions, cities -and those living in them by directing material, energy and value flows from poorer places (Jones, 2015;Hickel et al 2022), but these resources and the capitals that generate them are degrading in the face of climate change and the over-exploitation of nature. Novel tensions and areas of conflict are emerging, not just with respect to who 'owns' and benefits from increasingly scarce resources, but also in terms of who national and supra-national regulation, and environmentally-oriented trading schemes, will advantageand who can prepare best to take advantage (Jones & Munday, 2020;McAfee, 2022). These tensions are becoming clear in resource rich and (relatedly) relatively poor regions in South and Northand with transnational actors increasingly visible in processes that shape places to capture new and diminishing value, and insure against regulatory and industrial change (Hein et al, 2019;Bueno et a, 2018;Beauchamp & Jenkins, 2020;Feldman et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The control over embedded resources enjoyed by placeless actors is increased by inequality. In societies where the redistribution of income and (especially) wealth is limited, or where there is an increasing concentration of market share in individual or oligopolistic firms; 'one dollar one vote' means that key, immobile resources (including energy, land, and human capital) will be subject to bidding wars where well-resourced placeless actors move first or bid highest (Jones & Munday, 2020;Orefice et al, 2015).…”
Section: Large Scale and Inequitable Socio-economic Structures Reward...mentioning
confidence: 99%
“…The focus on inherited problems of low skills, relatively low urbanisation and weak infrastructure connectivity represent ‘an argument for realism, not an expression of complacency’ (Price, 2016, p. 48) which will take a long time to address. Kapitsimis et al (2021) also highlight the low Small and Medium Sized Enterprise (SME) equity problem, rooted in both low demand and poor supply, particularly outside Cardiff, and Jones and Munday (2020) highlight the continuing lack of dynamic private sector leadership arising when capital ownership is outside Wales. Bristow (2018) stressed what she called the remanence of Wales’ experience of late twentieth century de-industrialisation, dependent upon cost-sensitive external investment and lacking diverse strengths.…”
Section: Conventional Wisdoms and Rethinking Regional Economic Develo...mentioning
confidence: 99%
“…There has been little fundamental change in the relative underperformance of the Welsh economy, whether measured in terms of wealth, economic activity, productivity, employment or wage levels. There is still though a relatively limited debate on the causes of Welsh economic performance since devolution: comprising in the main analyses that stress the importance of long-term structural problems to explain much of contemporary performance (Bristow, 2018; Jones and Munday, 2020; Kapitsimis et al, 2021; Price, 2016); critiques of the context of UK political economy which despite devolution has still remained fundamentally important and has failed to deliver redistributive public expenditure that could make a difference (Morgan, 2006); and constitutionalist-left critiques of the extent of devolved powers and inability of Welsh Government to break from the dominant influence of UK Government and neoliberalism (Evans et al, 2021). These are all at root apologias for what Welsh devolution has been able to achieve.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study in Wales, UK, that investigated the complex investment in energy and other industries showed that success is also related to the amount of local capital. Therefore, when the regional investment falls short, investment is more likely to be handled at the national level than locally to maintain its sustainability [97].…”
mentioning
confidence: 99%